Metal–organic framework sensors for sustainable agriculture and environmental monitoring: Engineering, mechanisms, and future perspectives - Irfan Haidri; Muhammad Qasim; Qudrat Ullah; Muhammad Ali Amir; Waqas Haider; Hien Huu Nguyen; Athakorn Promwee (Environmental Nanotechnology, Monitoring & Management, 2026)

Retraction Note: Exploring the molecular mechanisms of rice blast resistance and advances in breeding for disease tolerance - Muhammad Usama Younas; Muhammad Qasim; Irshad Ahmad; Zhiming Feng; Rashid Iqbal; Xiaohong Jiang; Shimin Zuo (Molecular Biology Reports, 2026)

Geology of the Oligocene-Neogene Dhofar Group (Ma'ahm Beds and Barzaman Formation, NE Oman) and its alteration and tectono-sedimentary evolution - Andreas Scharf; Musaab Al-Sarmi; Ivan Callegari; Abdul Razak Al-Sayigh; Frank Mattern; Behzad Mehrabi; Muhammad Qasim; Arshad Ali; Abdul Majeed Al-Shuaili (Journal of African Earth Sciences, 2026)

Retraction Note: Integrating physiological and molecular insights in cotton under cold stress conditions - Aamir Ali Abro; Muhammad Qasim; Mubashir Abbas; Noor Muhammad; Ijaz Ali; Shiguftah Khalid; Junaid Ahmed; Muhammad Waqas; Sezai Ercisli; Rashid Iqbal; Fang Liu (Genetic Resources and Crop Evolution, 2026)

Assessment of railway earthworks using DAS based active MASW surveys - Muhammad Saqlain; Andrew Trafford; Qasim Khan; Ben Dashwood; Jonathan E. Chambers; Gavin Jessamy; Julian Harms; Shane Donohue (Transportation Geotechnics, 2026)

Retraction Note: Impact of elevated temperatures on the genetic and morpho-physiological traits of cotton genotypes cultivation - Aamir Ali Abro; Muhammad Qasim; Muhammad Usama Younas; Ijaz Ali; Mubashir Abbas; Noor Muhammad; Shiguftah Khalid; Junaid Ahmed; Umbreen Bibi; Muhammad Waqas; Sezai Ercisli; Fahad Al-Asmari; et al. (Genetic Resources and Crop Evolution, 2026)

Bio-based modification of recycled concrete aggregate for cover systems: eco-hydro-mechanical performance evaluation - Jiayu Gu; Jingsong Zhou; Junjun Ni; Muhammad Qasim; Saif Ullah (Waste Management, 2026)

Revealing the complete chloroplast genome of Camptostemon philippinensis, an aid in the adoption of conservation strategies of endangered species - Istiana Prihatini; Arief Priyadi; Risha Amilia Pratiwi; Fitri Indriani; A.Y.P.B.C. Widyatmoko; I.L.G. Nurtjahjaningsih; Irfan Martiansyah; Tri Atmoko; Mukhlisi; Burhanuddin Adman; Abdul Razaq Chasani; Muhammad Uzair Qasim (Plant Gene, 2026)

Bioadaptive metal–organic frameworks in sustainable agriculture: Integrated crop protection, nutrient delivery, and beneficial microbial protection - Irfan Haidri; Muhammad Qasim; Qudrat Ullah; Ebadet Ali; Muhammad Ali Amir; Waqas Haider; Athakorn Promwee (Physiological and Molecular Plant Pathology, 2026)

Nonlinear water wave dynamics of data-driven soliton solutions for the Kakutani–Matsuuchi model in Ocean Engineering - Muhammad Qasim; Tahir Shahzad; Fengping Yao; Muhammad Zafarullah Baber; Nauman Ahmed (Ocean Engineering, 2026)

Machine learning–enhanced framework of complex nonlinear wave dynamics in oceanic atmosphere - Muhammad Qasim; Muhammad Zafarullah Baber; Yakup Yildirim; Adil Jhangeer; Muhammad Waqas Yasin (Ocean Engineering, 2026)

Modeling complex ocean wave patterns through a time-fractional Clannish Random Walker’s Parabolic equation using a neural network-assisted bilinear approach - Muhammad Zafarullah Baber; Muhammad Qasim; Fengping Yao; Yakup Yildirim (Ocean Engineering, 2026)

Synergistic regulation of cadmium tolerance by a 2 C protein phosphatase and nano molybdenum by modulating cellular structure, metal transport, and redox homeostasis in polyploid rice - Muhammad Qasim Shahid; Zihang Lin; Lixia Sun; Zhen Li; Muhammad Farooq; Fozia Ghouri (Journal of Hazardous Materials, 2026)

Cyclic Use of Wastewater and Canal Water Improves Maize Growth while Reducing Heavy Metal Accumulation in Soil - Shaikh Amjad Salam; Muhammad Qasim; Hossam S. El-Beltagi; Usman Zulfiqar; Mohammed S. Alotaibi; Nozimakhon Khodjimurodova; Kabulzhan Azizov; Nazih Y. Rebouh (Water, Air, & Soil Pollution, 2026)

Multi-omics and precision breeding strategies for enhancing biotic and abiotic stress resilience in rice - Zameer Hussain Jamali; Muhammad Usama Younas; Muhammad Qasim; Sajad Ali; Rashid Iqbal; Saltanat Aghayeva; Petr Konvalina (Cereal Research Communications, 2026)

Plant-Nanotechnology 4.0: AI, Biosensors, and Smart Nanomaterials for Climate Resilient Agriculture - Muhammad Qasim; Rida Batool; Irfan Haidri; Qudrat Ullah; Thanet Khomphet; Maaz Ullah; Sayanti Mandal (Journal of Soil Science and Plant Nutrition, 2026)

Biochemical analysis and antimicrobial potential of Mastacembelus armatus epidermal mucus - Muhammad Saeed Khan; Shandana Ali; Muhammad Qasim; Farman Ullah Dawar; Waheed Ullah (Journal of Fish Biology, 2026)
The epidermal mucus of fish plays an important role in innate immunity, providing both physical and biochemical protection through a complex matrix of bioactive molecules. The present study explored the biochemical characterization, bactericidal, and fungicidal activities of Mastacembelus armatus (Zig‐Zag eel) epidermal mucus treated with Aeromonas hydrophila . Extracts of epidermal mucus (ethanolic and acidic) of Mastacembelus armatus showed antimicrobial activity against selected resistant bacteria and fungi. The zone of inhibition (ZOI), which was measured in millimetres, revealed differences in activity between different fungi and bacteria. The acidic extract demonstrated noticeably higher ZOI values against various MDR bacteria and fungi was more effective than the ethanolic extract. Strong peaks in the Fourier transform infrared (FTIR) spectrum of Mastacembelus armatus indicated the presence of metabolic components in the epidermal mucus. The O–H and N–H stretching vibrations, which are indicative of water content and protein‐based molecules such as mucins or amide, are shown by a large peak at 3272.60 cm −1 . This result suggests that fish epidermal mucus has the potential to contribute enormously to the defence of fish against bacteria and fungi. Therefore, this study could be evidence in favour of the substitution of chemical antibiotics with fish epidermal mucus as a new ‘antimicrobial’ introduced in aquaculture and in humans against bacterial infections.

Modeling fractional wave propagation in ocean engineering: Neural network solutions for the clannish random walker’s parabolic equation - Muhammad Qasim; Fengping Yao; Muhammad Zafarullah Baber; Adil Jhangeer (Ocean Engineering, 2026)

Rice 2C protein phosphatase, OsNY1, and magnesium oxide positively regulate arsenic tolerance by root cells reinforcement, metals detoxification, and protein phosphorylation - Zihang Lin; Lixia Sun; Weiwei Xia; Zhen Li; Fozia Ghouri; Muhammad Qasim Shahid (Journal of Hazardous Materials, 2026)

Impact of insect socialism on the ecology and management of ambrosia beetles - Neslihan Gültekin; Melek Güçlü; Dilbar Hussain; Sumaira Maqsood; Levent Gültekin; Muhammad Qasim (Arthropod-Plant Interactions, 2026)

Plant growth-promoting rhizobacteria (PGPR) producing ACC deaminase and exopolysaccharides enhance salt tolerance in wheat - Mahnoor Hayat; Rashida Parveen; Muhammad Shoib Nawaz; Muhammad Ahmad Rao; Ahmed Waqar; Rubab Zahra. Naqvi; Munir Ahmad Anwar; Zahir Ahmad Zahir; Muhammad Qasim; M Ahmad Dogar; Tadeo Sáez Sandino; Brajesh K. Singh; et al. (World Journal of Microbiology and Biotechnology, 2026)

Modeling groundwater dynamics in a low-lying sedimentary island driven by recharge variability, climate change, and water demand - Muhammad Qasim Mahmood; Xiuquan Wang; Farhan Aziz; Qing Li; Nadeem Tariq (Journal of Hydrology, 2026)

From barns to atmosphere: Pakistan's livestock manure-derived NH3, N2O, and CH4 emissions (1961–2022) and cleaner production pathways - Syed Qasim Ali Shah; Noor Haleem; Chaudary Muhammad Haris; Leena Khan; Yousuf Jamal; Humayoun Akram; Xufei Yang (Journal of Cleaner Production, 2026)

Phylogeny and diversity study in Damani sheep through mitochondrial DNA D-loop nucleotides sequence - Muhammad Zohaib; Farhad Ali; Syed Muhammad Suhail; Rajwali Khan; Muhammad Tariq Zeb; Ihsan Ali; Mohammad Qasim; Khalid Khan; Iftikhar Ahmad; Ijaz Ahmad (Tropical Animal Health and Production, 2026)

The Evolution of Organoids: From Discovery to Cutting-Edge Applications - Javeria Umber; Uzair Ahmed; Tazeem Fatima; Muhammad Qasim; Usman Ali Ashfaq; Muhammad Shareef Masoud (Stem Cell Reviews and Reports, 2026)

Electrothermally regenerable electrospun MXene-PLA composite filters with multi-stage smart filtration - Muhammad Kashif; Muhammad Qasim; Yong Liu (Journal of Environmental Chemical Engineering, 2026)

Oryza rufipogon and diosgenin alleviate cadmium toxicity by limiting grain translocation in rice: Insights from molecular and physiological regulation mechanisms - Minghui Zhong; Zhen Li; Lixia Sun; Shafaqat Ali; Weiwei Xia; Jingwen Liu; Jiacheng Jin; Muhammad Qasim Shahid; Fozia Ghouri (Journal of Environmental Sciences, 2026)

In vitro culture studies and the effect of ZnO and CuO nanoparticles on total phenolic content expression in psoralea corylifolia - Sarah Ali; Saboohi Raza; Amna Ahmed; Muhammad Abdul Haq; Beena Siddiqua; Qasim Khan (In Vitro Cellular & Developmental Biology - Plant, 2026)

Phosphorus-laden biochar modulates soil microbial communities and promotes phosphorus cycling in acidic soils - Zeinab El-Desouki; Yehia Abouseif; Jiyuan Wang; Muhammad Qasim; Saba Babar; Xiaoyang Xia; Xiangling Wang; Cuncang Jiang (Applied Soil Ecology, 2026)

Slow-Release DAP Fertilizer Coated with Bacillus velezensis FB2 and Polyvinyl Alcohol for Sustainable Maize Production - Zumrah Rehman; Muhammad Bilal Khan Niazi; Zaib Jahan; Ghulam Abbas Shah; Hazrat Ali; Zia Ur Rahman Farooqi; Waqas Mohy-Ud-Din; Qasim Ali; Gamal Awad El-Shaboury; Haitham Ibrahim El-Mekkawy (Journal of Soil Science and Plant Nutrition, 2026)

A combined field and laboratory investigation into the moisture dependency of Vs for a clay-rich railway embankment fill - Qasim Khan; Muhammad Saqlain; Andrew Trafford; Ben Dashwood; J.E. Chambers; Gavin Jessamy; Julian Harms; Shane Donohue (Engineering Geology, 2026)

A mixed carbonate-siliciclastic foreland basin system: An example from the Upper Cretaceous Muti Formation, Jabal-Akhdar Dome, Oman Mountains - Jenan Ahmed Attar; Iftikhar Ahmed Abbasi; Muhammad Hanif; Mohamed A. K. El-Ghali; Abdulrazaq Al-Sayigh; Mohamed S. H. Moustafa; Muhammad Qasim (Facies, 2026)

Identification of a novel mutation of sat (Gly82Arg) in Shigella flexneri serotype 7a: insights into clinical relevance - Iqbal Nisa; Muhammad Qasim; Arnold Driessen; Jeroen Nijland; Hazir Rahman; Yasar Mehmood Yousafzai; Khalid J. Alzahrani; Jochen Mattner; Niaz Muhammad; Fazli Bari; Taj Ali Khan (Folia Microbiologica, 2026)

Synergistic effects of zinc and reduced glutathione application on growth, yield, gas exchange attributes, water relations, and metabolite profiles in Zea mays (L.) plants under water deficit irrigation - Farah Saeed; Qasim Ali; Suliman Mohammed Suliman Alghanem; Abida Kausar; Rashida Perveen; Haifa Abdul Aziz Sakit Alhaithloul; Muhammad Rizwan (South African Journal of Botany, 2026)

Unearthing potential of aluminum-modified biochar for saline-alkali soil rejuvenation and microbial diversity enhancement - Saba BABAR; Amanullah BALOCH; Muhammad QASIM; Jiyuan WANG; Xiangling WANG; Rashid IQBAL; Ali M. ABD-ELKADER; Khurram SHEHZAD; Xiaoyang XIA; Cuncang JIANG (Pedosphere, 2026)

Retraction Note: Salinity effects on growth, biomass production, and genetic resources for phytoremediation potential of halophyte species in the desert - Muhammad Abid; Muhammad Rafay; Tanveer Hussain; Muhammad Azeem Sabir; Muneeb Khalid; Muhammad Madnee; Hussain Ahmed Makki; Muhammad Qasim; Ehab I. Taha; Mounir M. Bekhit; Rashid Iqbal (Genetic Resources and Crop Evolution, 2026)

Retraction Note: Understanding rice blast: investigating biotechnological methods to speed up the development of robust rice cultivars - Nimra Rajput; Muhammad Usama Younas; Muhammad Qasim; Saima Parveen Memon; Shabana Memon; Magda Abd El-Rahman; Saltanat Aghayeva; Sezai Ercisli; Rashid Iqbal; Shimin Zuo (Genetic Resources and Crop Evolution, 2026)

Retraction Note: Morphological and genetic diversity of barley (Hordeum vulgare L.) germplasm - Ayaz Ali; Rahman Ullah; Saeed Anwar; Ahmad Ali; Zahid Ullah; Hassan Sher; Javed Iqbal; Banzeer Ahsan Abbasi; Dunia A. Al Farraj; Mohamed S. Elshikh; Muhammad Qasim; Rashid Iqbal (Genetic Resources and Crop Evolution, 2026)

Integrative Molecular and Structural Profiling of Escherichia coli Virulence Genes in Diabetes-Associated Infections - Noor Jahan Begum; Muhammad Qasim; Ihtisham Ul Haq; Hassan Naveed; Farhan Anwar Khan; Zahid Ullah Khan; Farman Ullah Dawar (Current Microbiology, 2026)

Agricultural Waste Valorisation in Gulf Countries: A Scoping Review Toward Circular Economy and Sustainable Policy Innovation - Nur Fathin Ruslan; Noormazlinah Ahmad; Mimi Sakinah Abdul Munaim; Mohd Zamri Che Wanik; Antonio Sanfilippo; Jayaprakash Saththasivam; Muhammad Qasim Ali (Circular Economy and Sustainability, 2026)

Improving Wheat Production in Pakistan Through an Economically Viable Solar‐Powered Rain Gun Sprinkler Irrigation System - Muhammad Asif; Shahzad Hussain Dahri; Bashir Ahmad; Noman Latif Sadozai; Sohail Raza Haidree; Abdul Hannan; Syed Qasim Ali Naqvi (Irrigation and Drainage, 2026)
In rainfed agriculture, limited water availability has become a challenging factor for sustainable farming and economic security. For regions with variable climate conditions, efficient water management practices must be adopted to improve livelihoods and food security. This study aimed to evaluate the role of supplemental irrigation for wheat crops in the Pothwar region. The irrigation management consists of I 0 (rainfed), I 1 (10 mm presowing), I 2 (10 mm at 50% soil moisture depletion [SMD]) and I 3 (25 mm at 75% SMD). The results revealed that, under I 3 , the grain yield increased by 49% and 17%, followed by I 2 (47% and 12%) compared to the rainfed yield of 1.85 and 3.93 tons/ha in Jand and NARC, respectively. The analysis of variance and Tukey's honestly significant difference (HSD) test revealed that the yield for I 0 value was significantly lower than that of all the irrigation treatments, while there were no significant differences among I 1 , I 2 and I 3 . The net benefit analysis revealed that I 3 was an economic irrigation schedule and paid back the total intervention cost by generating PKR 389,915/ha at NARC and PKR 283,915/ha at Jand in 3.83 and 4.93 years, respectively. This viable economic return makes solar‐powered irrigation systems reliable sources of water for water‐scarce and climate‐variable regions.

Polyploidy and zinc nanoparticles enhanced cadmium tolerance by regulating antioxidants and transport proteins - Jingwen Liu; Fozia Ghouri; Lixia Sun; Zihang Lin; Minghui Zhong; Muhammad Farooq; Muhammad Qasim Shahid (Plant Cell Reports, 2026)

Optimizing Phosphorus Use Efficiency and Fodder Yield of Pearl Millet: Two-Year Field Evaluation of Phosphorus-Solubilizing Bacteria with Inorganic Fertilizer Under Alkaline-Calcareous Soils - Abdul Majeed; Qasim Ali; Muhammad Haseeb Javaid; Muhammad Naveed; Mubshar Hussain (International Journal of Plant Production, 2026)

Eco-Friendly Synthesis of Magnesium Oxide Nanoparticles Using Citrullus colocynthis and their Synergistic Antimicrobial Activity against Drug-Resistant Pathogens - Maqsood Qaisar; Abdul Rehman; Iffat Naz; Hassan Naveed; Baharullah Khattak; Muhammad Qasim (Current Microbiology, 2026)

Combined use of proline and microbes on yield attributes, photosynthetic efficiency, water relations, nutrient acquisition and antioxidative defense mechanisms of fennel plants under drought conditions - Tabish Ali Virk; Muhammad Zulqurnain Haider; Qasim Ali (Biologia Futura, 2026)

Genomic surveillance of Influenza, SARS-CoV-2, and RSV in patients from Islamabad and Rawalpindi, Pakistan: a 2023-24 perspective - Zunera Jamal; Syed Adnan Haider; Fahad Humayun; Qasim Ali; Rabia Hakim; Muhammad Salman; Massab Umair (Archives of Virology, 2026)

Eco-applicable pectinase from Bacillus infantis (SA2): enzyme production, optimization, protein profiling, and pesticide degradation approaches using molecular docking - Arul Dhayalan; Sumathi Manoharan; Mohammed Qasim Waheeb; Muhammad Fazle Rabbee; Natarajan Thillainathan (Archives of Microbiology, 2026)

Timing of India-Asia diachronous collision: A view from the westernmost Indian margin, Pakistan - Muhammad Qasim; Owais Tayyab; Lin Ding; Javed Iqbal Tanoli; Muhammad Awais; Kamran Tabassum; Fulong Cai; Zhang Dingding; Ishtiaq A.K. Jadoon (Tectonophysics, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Remediation of Water Contaminated by Toxic Metals with Multi-metal/Co-doped Modified Biochars - Ghulam Murtaza; Muhammad Usman; Zeeshan Ahmed; Muhammad Qasim; Javed Iqbal; Shabir Ahmad; Rashid Iqbal; Lala Gurbanova; Mehdi Rahimi (Water, Air, & Soil Pollution, 2026)

Effect of Hong Huang Tang on memory enhancement and mitigation of microgravity-induced oxidative stress in C. elegans - Inam Ullah; Muhammad Zulqarnain Shakir; Xu Chen Zhou; Jixian Liu; Shilan Li; Huabiao Chen; Ning Jiang; Muhammad Wasim Usmani; Muhammad Qasim Barkat; Qiaobei Du; Yufen Zhao; Ning Wang; et al. (Biogerontology, 2026)

Evaluation of resistance level of exotic cotton Gossypium hirsutum accession “Mac-07” against cotton leaf curl disease complex - Khalid Pervaiz Akhtar; Sajawal Iqbal; Najeeb Ullah; Muhammad Qasim Aslam; Muhammad Kashif Riaz Khan; Imran Amin (Journal of Plant Pathology, 2026)

Mechanistic insights into the synergistic pharmacology of quercetin–kaempferol against SARS-CoV-2 infection - Farman Ali; Muhammad Zubair Saleem; Muhammad Mohsin; Saleem Ahmad; Waqar Islam; Wasim Qasim; Muhammad Tayyab (In Silico Pharmacology, 2026)

Seed Priming with Osmolytes Ameliorates Salinity Tolerance in Maize (Zea mays L.) Through Embryonic Modifications - Paris Riaz; Ansa Asghar; Sana Fatima; Sana Basharat; Zahida Parveen; Mansoor Hameed; Farooq Ahmad; M. Sajid Aqeel Ahmad; Muhammad Ashraf; Faakeha Islam; Syed Mohsan Raza Shah; Qasim Ali (Journal of Plant Growth Regulation, 2026)

Performance comparison of complete mix reactor and static mixer in ballasted flocculation - Muhammad Qasim; Muhammad Naveed Afridi; Salman Ali Suhail; Usman Pervaiz Khan; Imtiaz Afzal Khan; Jong-Oh Kim (Chemosphere, 2025)

Amino acid functionalized graphene oxide nanocomposite with enhanced adsorption capacity towards methyl orange dye: Insights into kinetics and mechanism - Uzaira Jameel; Muhammad Naveed Qasim; Afnan Qabil Alshammari; Naseem Ahmad Khan; Muhammad Mateen; Behzodjon D. Mamatkodirov; Bakhtiyar T. Ibragimov; Xusheng Wang; Muhammad Nadeem Akhtar (Journal of Water Process Engineering, 2025)

Genetic Mechanisms and Improvement Strategies for Rice Sheath Blight Resistance - Muhammad Usama Younas; Bisma Rao; Muhammad Qasim; Irshad Ahmad; Zhiming Feng; Saima Parveen Memon; Rashid Iqbal; Shimin Zuo (Plant Molecular Biology Reporter, 2025)

Beyond traditional diagnosis: aptamer-based microRNA detection for the early diagnosis of periodontitis - Muhammad Usman Ashraf; Khairul Mohd Fadzli Mustaffa; Nurul Wahida Mohd Hasan; Maaz Anwer Memon; Danial Qasim Butt; Rizwan Mahmood; Wan Nazatul Shima Shahidan (Molecular Biology Reports, 2025)

Green Synthesis, Characterization, and Effect of Zinc Oxide Nanoparticles on Wheat (Triticum Aestivum L.) Under Cadmium Stress - Aqsa Khan; Samina Jam Nazeer Ahmad; Muhammad Jafir; Adeel Ahmad; Muhammad Irfan; Muhammad Qasim; Jam Nazeer Ahmad; Muhammad Azeem Sabir; Muhammad Faisal Maqsood; Abdul Rehman; Waleed A. A. Alsakkaf; Hayssam M. Ali (Journal of Soil Science and Plant Nutrition, 2025)

Integrated Phosphorus Management and Bacillus Cereus MN54 Inoculation Improve Fodder Yield, Nutrient Use Efficiency and Economic Returns in Pearl Millet Grown in Calcareous Soils - Abdul Majeed; Qasim Ali; Muhammad Naveed; Mubshar Hussain (Journal of Soil Science and Plant Nutrition, 2025)

Faunistics of Syrphid flies (Diptera: Syrphidae) from Chakesar Valley, District Shangla, Pakistan and their biogeographic association - Waqas Ahmad; Jalal Hayat Khan; Qudrat Ullah; Khalid khan; Muhammad Zubair; Sumara Aslam; Muhammad Qasim; Muhammad Ather Rafi (International Journal of Tropical Insect Science, 2025)

Bacillus Inoculation Along with Biogas Slurry Mitigates Nickel Stress in Raphanus Sativus by Regulating Ni Accumulation and the Antioxidant Defense System - Iftikhar Ahmad; Shehzad Mehmood; Muhammad Atif Muneer; Aftab Jamal; Amjad Farooq; Muhammad Farhan Saeed; Qasim Ali; Umar Daraz; Nabil Touzout; Adil Mihoub; Jun Zhou (Water, Air, & Soil Pollution, 2025)

Diversity of arthropods fauna in correlation to abiotic factors in wheat crop - Dilbar Hussain; Bushra Khalid; Muhammad Asrar; Usama Saleem; Wafa Abdullah Hamad Alkherb; Muhammad Saleem; Hina Anwar; Saddam Hussain; Muhammad Sohail Qadir; Mubshar Saleem; Khalid Ali Khan; Hamed A. Ghramh; et al. (International Journal of Tropical Insect Science, 2025)

Selection criteria for the enhancement of nitrogen use efficiency in wheat using two step association analysis - Muhammad Amjad; Siddique Ahmad; Fahim Ullah Khan; Rafi Ullah; Iltaf Ullah; Muhammad Zahid Shah; Umar Bin Qasim (Vegetos, 2025)

Xanthan gum coating delays ripening of harvested mango (Mangifera indica L.) fruit by suppressing chlorophyll catabolism and cell wall polysaccharides degradation - Maimona Qasim; Sajid Ali; Hafiz Umer Javed; Safina Naz; Ahmad Sattar Khan; Muhammad Hassan; Rana Naveed Ur Rehman (Postharvest Biology and Technology, 2025)

Genome-wide identification, characterization and expression analysis of CsC3H gene family in cucumber (Cucumis sativus L) under various abiotic stresses - Saleem Uddin; Sadia Gull; Hafiz Athar Hussain; Umer Mahmood; Muhammad Qasim; Farah Kamal; Abdel-Rhman Z. Gaafar; Saltanat Aghayeva; Rashid Iqbal; Xiaohong Yang (Plant Science, 2025)

Integrated Approaches for Enhancing Magnaporthe oryzae Resistance: Mechanisms and Breeding Strategies - Muhammad Usama Younas; Muhammad Qasim; Irshad Ahmad; Zhiming Feng; Rashid Iqbal; Tanweer Fatah Abro; Shabir Ahmad; Xiaohong Jiang; Nimra Rajput; Shimin Zuo (Plant Molecular Biology Reporter, 2025)

Comparative Efficacy of Different Rice (Oryza sativa L.) Genotypes for Improved Zinc and Iron Uptake and Relevant Yield Efficiency under their Foliar Application - Shafiq ur Rahman Memon; Saima Parveen Memon; Muhammad Qasim; Huagang Huang; Abd El-Zaher M. A. Mustafa; Mohamed S. Elshikh; Rashid Iqbal; Zicheng Zheng (Journal of Soil Science and Plant Nutrition, 2025)

Femtosecond laser-structured waste cardboard: Simultaneously separating oil/water emulsions and removing viscous oil with solar energy - Muhammad Qasim; Hamzeh Sabouni; Ganjaboy S. Boltaev; Ali S. Alnaser (Journal of Cleaner Production, 2025)

Assessing human health risks associated with wastewater flooding - Farhan Aziz; Xiuquan Wang; Muhammad Qasim Mahmood; O’Keeffe Juliette (Environmental Impact Assessment Review, 2025)

Utilizing genetic resources to develop yellow rust-resistant and high-yielding wheat genotypes across diverse environments - Hassan Mujtaba; Fahim Ullah Khan; Muhammad Sufyan; Israr Ud Din; Manzoor Ahmad; Asad Shah; Umair Bin Qasim (Genetic Resources and Crop Evolution, 2025)

Exploration of biochars for enhancing soil health, carbon sequestration, and greenhouse gas emission reductions under citrus cultivation - Muhammad Qasim; Saba Babar; Muhammad Usama Younas; Nimra Rajput; Xiaoyang Xia; Jiyuan Wang; Xiangling Wang; Cuncang Jiang (European Journal of Agronomy, 2025)

Detrital zircon U–Pb geochronology of the Murree Formation, western Himalaya, Pakistan: provenance and tectonic implications for Himalayan exhumation - Muhammad Qasim; Fozail Khan; Lin Ding; Iftikhar Ahmed Abbasi; Andreas Scharf; Fulong Cai (International Geology Review, 2025)

Cytological observation and transcriptome analysis reveal that NTFR1 is a new tetraploid rice fertility gene using the tetraploid fertility-directed lines - Hao Fan; Kai Li; Mengzhu Hu; Zijuan Huang; Haibin Guo; Xiang Li; Zhixiong Chen; Lan Wang; Muhammad Qasim Shahid; Xiangdong Liu; Jinwen Wu (Plant Science, 2025)

Metabolomic, biochemical, and cytological observations reveal β-Pinene's protective effects against cadmium toxicity in salt-tolerant rice - Fozia Ghouri; Jiacheng Jin; Shafaqat Ali; Minghui Zhong; Jingwen Liu; Weiwei Xia; Fengliang Jin; Muhammad Qasim Shahid (Journal of Environmental Management, 2025)

Biochar amendment modulate microbial community assembly to mitigate saline-alkaline stress across soil depths - Xiangling Wang; Xiaoyang Xia; Muhammad Riaz; Saba Babar; Zeinab El-Desouki; Muhammad Qasim; Jiyuan Wang; Cuncang Jiang (Journal of Environmental Management, 2025)

Epidemiology and genetic characterization of Alternaria alternata causing leaf spot in Fragaria × ananassa - Nasir Mehmood; Abid Riaz; Salman Ghuffar; Sadaf Anwaar; Nyla Jabeen; Isha Shaheen; Muhammad Qasim; Salma Saeed Khan; Muhammad Rauf; Tauseef Anwar; Huma Qureshi; Ghadah Salim Abusalim; et al. (Fungal Biology, 2025)

Urban flood modelling: Challenges and opportunities - A stakeholder-informed analysis - Muhammad Qasim Mahmood; Xiuquan Wang; Farhan Aziz; Nilay Dogulu (Environmental Modelling & Software, 2025)

Biochar and Pseudomonas aeruginosa M2 Co-Application: A Sustainable Strategy for Enhancing Growth and Heavy Metal Tolerance in Brassica campestris - Muhammad Muzammil Mukhtar; Qasim Ali; Muhaimen Ayyub; Muhammad Aon; Hayssam M. Ali; Sadaf Oranab; Iftikhar Ahmad; Ghulam Abbas; Behzad Murtaza; Waqas Mohy-Ud-Din; Usman Zulfiqar; Muhammad Faisal Maqsood; et al. (Journal of Soil Science and Plant Nutrition, 2025)

Fe-Modified Biochar Improves Tobacco Productivity by Promoting Root Growth, Plant Biochemical Traits and Nicotine Level: A Three Years Field Study - Ghulam Murtaza; Muhammad Usman; Qamar uz Zaman; Zeeshan Ahmed; Mona S Alwahibi; Humaira Rizwana; Javed Iqbal; Muhammad Qasim; Rashid Iqbal; Gang Deng (Journal of Soil Science and Plant Nutrition, 2025)

Nitric Oxide and Hydrogen Peroxide Coordinate to Improve Photosynthesis, Oxidative Defense, Osmoregulation, and Ions Homeostasis in Pea (Pisum sativum L.) Under Drought - Muhammad Kamran Afzal; Noman Habib; Muhammad Arslan Ashraf; Qasim Ali; Shafaqat Ali (Journal of Soil Science and Plant Nutrition, 2025)

Combined Application of Compost and Biogas Residues Reduces Soil and Pore Water Metal Concentration and Their Residual Toxicity to Wheat Seedlings - Iftikhar Ahmad; Ghulam Mustafa Shah; Hafiz Muhammad Shahbaz; Aftab Jamal; Muhammad Imtiaz Rashid; Muhammad Farhan Saeed; Amjad Farooq; Qasim Ali; Domenico Ronga (Journal of Soil Science and Plant Nutrition, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Energy metabolism, antioxidant defense system, metal transport, and ion homeostasis are key contributors to Cd tolerance in SSSL derived from wild rice - Humera Ashraf; Fozia Ghouri; Lixia Sun; Weiwei Xia; Sawaira Ashraf; Muhammad Zahid Ashraf; Xuelin Fu; Shafaqat Ali; Muhammad Qasim Shahid (Journal of Hazardous Materials, 2025)

PFAS insights: A review of historical data, environmental applications, health effects, and pollution challenges in Pakistan - Amna Chaudhary; Waqas Bashir; Abdul Majid; Muhammad Qasim; Erum Bughio; Minahal Fatima; Siraj U Din (Environmental Science & Policy, 2025)

Evaluation of genotoxicity and physicochemical variations of Eichhornia crassipes (Mart.) Solms exposed to paper-mill-contaminated wastewater - Harma Shah; Muhammad U. F. Awan; Zahid Mehmood; Noor Sana; Wasim Abbas; Adeel Ahmad; Abdullah Qasim; Annum Gul; Ali Hasnain; Hsi-Hsien Yang (Environmental Monitoring and Assessment, 2025)

Unraveling the synergistic effect of biochar and potassium solubilizing bacteria on potassium availability and rapeseed growth in acidic soil - Saba Babar; Amanullah Baloch; Muhammad Qasim; Jiyuan Wang; Xiangling Wang; Ali M. Abd-Elkader; Zeinab El-Desouki; Xiaoyang Xia; Cuncang Jiang (Journal of Environmental Management, 2025)

RETRACTED ARTICLE: ArticleNoteMorphological and genetic diversity of barley (Hordeum vulgare L.) germplasm - Ayaz Ali; Rahman Ullah; Saeed Anwar; Ahmad Ali; Zahid Ullah; Hassan Sher; Javed Iqbal; Banzeer Ahsan Abbasi; Dunia A. Al Farraj; Mohamed S. Elshikh; Muhammad Qasim; Rashid Iqbal (Genetic Resources and Crop Evolution, 2025)

RETRACTED ARTICLE: Salinity effects on growth, biomass production, and genetic resources for phytoremediation potential of halophyte species in the desert - Muhammad Abid; Muhammad Rafay; Tanveer Hussain; Muhammad Azeem Sabir; Muneeb Khalid; Muhammad Madnee; Hussain Ahmed Makki; Muhammad Qasim; Ehab I. Taha; Mounir M. Bekhit; Rashid Iqbal (Genetic Resources and Crop Evolution, 2025)

Integrating physiological and molecular insights in cotton under cold stress conditions - Aamir Ali Abro; Muhammad Qasim; Mubashir Abbas; Noor Muhammad; Ijaz Ali; Shiguftah Khalid; Junaid Ahmed; Muhammad Waqas; Sezai Ercisli; Rashid Iqbal; Fang Liu (Genetic Resources and Crop Evolution, 2025)

Morphological profiling and DNA barcoding revealed genetic diversity and phylogeny of Mentha species cultivated in Pakistan - Ismara Naseem; Muhammad Azam Khan; Umer Habib; Rashid Mehmood Rana; Muhammad Qasim; Mona S. Alwahibi; Rizwana Khanum; Muhammad Shafiq; Rashid Iqbal (Genetic Resources and Crop Evolution, 2025)

RETRACTED ARTICLE: Impact of elevated temperatures on the genetic and morpho-physiological traits of cotton genotypes cultivation - Aamir Ali Abro; Muhammad Qasim; Muhammad Usama Younas; Ijaz Ali; Mubashir Abbas; Noor Muhammad; Shiguftah Khalid; Junaid Ahmed; Umbreen Bibi; Muhammad Waqas; Sezai Ercisli; Fahad Al-Asmari; et al. (Genetic Resources and Crop Evolution, 2025)

Physicochemical profiling and health risk evaluation of effluents from textile industries: insights from Faisalabad, Pakistan - Hina Sattar; Muhammad Anwar-ul-Haq; Humera Aziz; Umair Riaz; Ahmad Mahmood; Muhammad Rizwan; Munaza Naseem; Mona S. Alwahibi; Mohamed S. Elshikh; Muhammad Qasim; Rashid Iqbal (Toxicology and Environmental Health Sciences, 2025)

Exogenous application of melatonin and jasmonic acid protects the sugar beet from heat stress by modulating the enzymatic antioxidants deference mechanism and accumulation of organic osmolytes - Muhammad Irfan; Ahmed Abou El-Yazied; Muhammad Sheeraz; Shabir Hussain; Abdul Sattar; Qasim Ali; Hany G. Abd El-Gawad; Fahad Mohammed Alzuaibr; Maha Mohammed Alharbi; Siham M. Al-Balawi; Doaa Bahaa Eldin Darwish; Eldessoky S. Dessoky; et al. (Acta Physiologiae Plantarum, 2025)

Maximizing heavy metal removal and precious metal recovery with innovative biowaste-derived biosorbents and biochar - Behzad Murtaza; Roshina Arshad; Moon Kinza; Jianxu Wang; Muhammad Shahid; Muhammad Imran; Noor S. Shah; Qasim Ali; Jibran Iqbal; Changseok Han (Process Safety and Environmental Protection, 2025)

Magnetically recyclable Mn and Co doped r-GO based LaFeO3 nano-composite for tuning the optical and solar light driven photo-catalytic applications - Shahid Iqbal; Muhammad Jamshaid; Firdous Bibi; Najla AlMasoud; Taghrid S. Alomar; Rashid Iqbal; Qasim Raza; Ambreen Kalsoom (Journal of Water Process Engineering, 2025)

Exploration of underutilized chayote fractions following drying and extraction - Ashiq Hussain; Faiza Iftikhar Gorsi; Muhammad Qasim Ali; Shazia Yaqub; Afifa Asif; Barira Bibi; Farooq Arshad; Ilaria Cacciotti; Sameh A. Korma (Food Chemistry, 2025)

Corrigendum to ‘The protective roles of Oryza glumaepatula and phytohormone in enhancing rice tolerance to cadmium stress by regulating gene expression, morphological, physiological, and antioxidant defense system’ [Environ. Pollut. 364P1 (2024) 125311] - Humera Ashraf; Fozia Ghouri; Shafaqat Ali; Syed Asad Hussain Bukhari; Fasih Ullah Haider; Minghui Zhong; Weiwei Xia; Xuelin Fu; Muhammad Qasim Shahid (Environmental Pollution, 2025)

Spatiotemporal pattern of climatic water balance over Balochistan, Pakistan for the period 1961–2016 - Muhammad Qasim; Kamal Ahmed; Aman Jan; Najeebullah Khan; Atif Muhammad Ali (Theoretical and Applied Climatology, 2025)

Evaluation of genetic diversity and population structure of the Chinese chestnut (Castanea mollissima) by using NR-SSR markers - Saman Zulfiqar; Muhammad Mahran Aslam; Allah Ditta; Rashid Iqbal; Abd El-Zaher M. A. Mustafa; Mohamed S. Elshikh; Muhammad Uzair; Saltanat Aghayeva; Muhammad Qasim; Sezai Ercisli; Ozhan Simsek; Tolga Izgu; et al. (Genetic Resources and Crop Evolution, 2025)

RETRACTED ARTICLE: Understanding rice blast: investigating biotechnological methods to speed up the development of robust rice cultivars - Nimra Rajput; Muhammad Usama Younas; Muhammad Qasim; Saima Parveen Memon; Shabana Memon; Magda Abd El-Rahman; Saltanat Aghayeva; Sezai Ercisli; Rashid Iqbal; Shimin Zuo (Genetic Resources and Crop Evolution, 2025)

Exploring environmentally stable and novel genetic factors influencing rice grain shape and yield attributes - Sadia Gull; Zulqarnain Haider; Houwen Gu; Saleem Uddin; Muhammad Qasim; Rana Ahsan Raza Khan; Adil Altaf; Sajid Fiaz; Mona S. Alwahibi; Mohamed S. Elshikh; Rashid Iqbal; Jun Miao; et al. (Euphytica, 2025)

Combined pharmacological and computational approaches unraveling the protective effects of Cassia angustifolia extract against NANO2 - induced neurodegeneration and hepatotoxicity - Shabina Ishtiaq Ahmed; Humaira Ismatullah; Qaisar Mansoor; Muhammad Yaseen; Aisha Naveed; Muhammad Qasim Hayat; Saadia Zahid; Junaid Arshad; Mubarra Tahir; Mashooq Ahmad Bhat (Food Bioscience, 2025)

The protective roles of Oryza glumaepatula and phytohormone in enhancing rice tolerance to cadmium stress by regulating gene expression, morphological, physiological, and antioxidant defense system - Humera Ashraf; Fozia Ghouri; Shafaqat Ali; Syed Asad Hussain Bukhari; Fasih Ullah Haider; Minghui Zhong; Weiwei Xia; Xuelin Fu; Muhammad Qasim Shahid (Environmental Pollution, 2025)

Revealing the effects of industrial structure upgrading and environmental technologies on environmental quality: Evidence from Asia - Jiang Zhi-qiang; Kong Ximei; Muhammad Qasim Javaid; Muhammad Sibt-e-Ali; Muhammad Zubair Chishti; Asif Ali (Environment, Development and Sustainability, 2024)

Rice and heavy metals: A review of cadmium impact and potential remediation techniques - Weiwei Xia; Fozia Ghouri; Minghui Zhong; Syed Asad Hussain Bukhari; Shafaqat Ali; Muhammad Qasim Shahid (Science of The Total Environment, 2024)

Coastal urban flood risk management: Challenges and opportunities − A systematic review - Farhan Aziz; Xiuquan Wang; Muhammad Qasim Mahmood; Muhammad Awais; Bill Trenouth (Journal of Hydrology, 2024)

Wastewater flooding risk assessment for coastal communities: Compound impacts of climate change and population growth - Farhan Aziz; Xiuquan Wang; Muhammad Qasim Mahmood; Ryan Guild (Journal of Hydrology, 2024)

Nutritional value and therapeutic potential of Moringa oleifera : a short overview of current research - Nabila Bibi; Nadia Rahman; Muhammad Qasim Ali; Noormazlinah Ahmad; Farzana Sarwar (Natural Product Research, 2024)

RETRACTED ARTICLE: Exploring the molecular mechanisms of rice blast resistance and advances in breeding for disease tolerance - Muhammad Usama Younas; Muhammad Qasim; Irshad Ahmad; Zhiming Feng; Rashid Iqbal; Xiaohong Jiang; Shimin Zuo (Molecular Biology Reports, 2024)

Allelic variation in rice blast resistance: a pathway to sustainable disease management - Muhammad Usama Younas; Muhammad Qasim; Irshad Ahmad; Zhiming Feng; Rashid Iqbal; Ashraf M.M. Abdelbacki; Nimra Rajput; Xiaohong Jiang; Bisma Rao; Shimin Zuo (Molecular Biology Reports, 2024)

Evaluation of carob tree (Ceratonia siliqua L.) pods, through three different drying techniques, and ultrasonic assisted extraction, for presence of bioactives - Ashiq Hussain; Muhammad Rehan Arif; Adnan Ahmed; Salah Laaraj; Nida Firdous; Muhammad Qasim Ali; Haya Fatima; Shazia Yaqub; Samina Kauser; Rizwan Nisar; Faiza Iftikhar Gorsi; Ghulam Mueen Ud Din; et al. (South African Journal of Botany, 2024)

Sustainable management in natural resources and carbon neutrality: Revisiting the nexus in Ukraine-Russia war context - Muhammad Shahzad Mubarik; Muhammad Kashif; Mubarra Shabbir; Qasim Jalil (Resources Policy, 2024)

A fuzzy multi-objective model for aggregate production planning considering energy consumption, carbon emission, chemical, solid waste, and wastewater - Muhammad Qasim; Kuan Yew Wong (Journal of Cleaner Production, 2024)

Geospatial intelligence in geotechnical engineering: a comprehensive investigation into SPT-N, soil types, and undrained shear strength for enhanced site characterization - Waqas Hassan; Muhammad Qasim; Badee Alshameri; Arfan Shahzad; Muhammad Hamza Khalid; Sana Ullah Qamar (Bulletin of Engineering Geology and the Environment, 2024)

Retraction Note: Exploring the nonlinear relationship among financial development, human capital and CO2 emissions: a comparative study of South and East Asian emerging economies - Muhammad Qasim Javaid; Kong Ximei; Muhammad Irfan; Muhammad Sibt-e-Ali; Tanzeela Shams (Environmental Science and Pollution Research, 2024)

Pluvial flood modeling for coastal areas under future climate change – A case study for Prince Edward Island, Canada - Quan Van Dau; Xiuquan Wang; Farhan Aziz; Rana Ali Nawaz; Tianze Pang; Muhammad Qasim Mahmood; Maxim Fortin (Journal of Hydrology, 2024)

Oryza glumaepatula and calcium oxide nanoparticles enhanced Cr stress tolerance by maintaining antioxidant defense, chlorophyll and gene expression levels in rice - Humera Ashraf; Fozia Ghouri; Minghui Zhong; Sardar Alam Cheema; Fasih Ullah Haider; Lixia Sun; Shafaqat Ali; Mohammed Ali Alshehri; Xuelin Fu; Muhammad Qasim Shahid (Journal of Environmental Management, 2024)

Corrigendum to “Defect-engineered dual Z-scheme core-shell MoS2/WO3-x/AgBiS2 for antibiotic and dyes degradation in photo and night catalysis: Mechanism and pathways” [Environ. Pollut. 356 (2024) 124375] - Muhammad Abbas; Mubashar Ilyas; Kashif Hussain; Tariq Ali; Muhammad Afzal; Nazia Batool; Navid Hussain Shah; Muhammad Qasim; Yaling Wang; Yanyan Cui (Environmental Pollution, 2024)

Defect-engineered dual Z-scheme core-shell MoS2/WO3-x/AgBiS2 for antibiotic and dyes degradation in photo and night catalysis: Mechanism and pathways - Muhammad Abbas; Mubashar Ilyas; Kashif Hussain; Tariq Ali; Muhammad Afzal; Nazia Batool; Navid Hussain Shah; Muhammad Qasim; Yaling Wang; Yanyan Cui (Environmental Pollution, 2024)

Spatio-temporal remote sensing evaluation of drought impact on vegetation dynamics in Balochistan, Pakistan - Atif Muhammad Ali; Haishen Lü; Yonghua Zhu; Kamal Ahmed; Muhammad Farhan; Muhammad Qasim (Theoretical and Applied Climatology, 2024)

Effects of drought on morpho-physiological attributes and secondary metabolites of wheat genotypes: Growth traits, seed yield and stress tolerance indices - Jazia Naseem; Qasim Ali; Farah Saeed; Rashida Perveen; Muhammad Rizwan (South African Journal of Botany, 2024)

Resources policy from extraction to innovation: The interplay of minerals, geothermal energy, technological advancements, and ecological footprint in high-ecological footprint economies - Muhammad Adnan Bashir; Li Qing; Qasim Raza Syed; Anna Barwińska-Małajowicz; Shabir Mohsin Hashmi (Resources Policy, 2024)

Evaluating the sustainability of groundwater abstraction in small watersheds using time series analysis - Muhammad Qasim Mahmood; Xiuquan Wang; Farhan Aziz; Tianze Pang (Groundwater for Sustainable Development, 2024)

Asymmetric effects of high-tech industry and presence of pollution-haven hypothesis in APEC countries: fresh evidence with panel quantile regression - Qasim Raza Khan; Ahsan Anwar; Tufail Muhammad; Noorulhaq Ghafoori; Mushtaq Ahmad (Clean Technologies and Environmental Policy, 2024)

In vitro exploration of Acinetobacter strain (SG-5) for antioxidative potential and phytohormone biosynthesis in maize (Zea mays L.) cultivars differing in cadmium tolerance - Saghir Abbas; Kashif Tanwir; Muhammad Hussaan; Sajid Masood; Qasim Ali; Ali Raza; Muhammad Shahid; Hassan Javed Chaudhary; Saba Mushtaq; Muhammad Tariq Javed (Environmental Science and Pollution Research, 2024)

Characterizing stalagmite composition using hyperspectral imaging - Ali Raza; Ny Riavo G. Voarintsoa; Shuhab D. Khan; Muhammad Qasim (Sedimentary Geology, 2024)

Exploring the phytochemical, antioxidant, antimicrobial and analgesic potentials of Solanum erianthum as an alternative biological feedstock for producing sustainable biochemicals - Muhammad Ajaib; Sairah Hafeez Kamran; Muhammad Faheem Siddiqui; Muhammad Qasim; Muhammad Azeem; Zainul Abideen; Attiat Elnaggar; Ali El-Keblawy (Biocatalysis and Agricultural Biotechnology, 2024)

Enhancing Plant Stress Resilience with Osmolytes and Nanoparticles - Yumna Rasheed; Faizan Khalid; Humaira Ashraf; Kanza Asif; Muhammad Faisal Maqsood; Nargis Naz; Muhammad Shahbaz; Usman Zulfiqar; Qasim Ali; Shamsa Rana (Journal of Soil Science and Plant Nutrition, 2024)

Greening the future: assessing the influence of technological innovation, energy transition and financial globalization on ecological footprint in selected emerging countries - Muhammad Sibt-e-Ali; Xia Xiqiang; Kashif Javed; Muhammad Qasim Javaid; László Vasa (Environment, Development and Sustainability, 2024)

Sustainable performance and disaster management in the oil and gas industry: An intellectual capital perspective - Sajid Nazir; Mahmood Ali; Munazza Saeed; Muhammad Shahzad Mubarik; Qasim Jalil (Resources Policy, 2024)

Visible light-activated curcumin-doped zinc oxide nanoparticles integrated into orthodontic adhesive on Micro-tensile bond strength, degree of conversion, and antibacterial effectiveness against Staphylococcus Aureus. An investigation using scanning electron microscopy and energy-dispersive X-ray spectroscopy - Abdullah A. Alnazeh; Muhammad Abdullah Kamran; Salem Almoammar; Mohammed Mohsen Al Jearah; Muhammad Qasim; Ibrahim Alshahrani (Journal of Photochemistry and Photobiology B: Biology, 2024)

Effects of pulsed Nd:YAG laser kernel irradiation on maize (Zea mays L.): Insights into germination, gas exchange, photosynthetic pigments, and morphological modifications - Rashida Perveen; Yasir Jamil; Arwa Abdulkreem AL-Huqail; Ibtisam Mohammed Alsudays; Suliman Mohammed Suliman Alghanem; Qasim Ali; Farah Saeed; Muhammad Azeem; Muhammad Rizwan; Sami Asir Al-Robai (Journal of Photochemistry and Photobiology B: Biology, 2024)

Serum and salivary Cu/Zn ratio as a diagnostic biomarker for oral submucosal fibrosis: an analysis of trace metals and LOX gene variants - Rafia Shah; Feriha Fatima Khidri; Yar Muhammad Waryah; Roohi Nigar; Amber Mahmood; Hina Shaikh; Muhammad Qasim Awan; Ikram Din Ujjan; Ali Muhammad Waryah (BioMetals, 2024)

Microorganism-mediated biodegradation for effective management and/or removal of micro-plastics from the environment: a comprehensive review - Hassan Zahid; Nimra Afzal; Muhammad Maaz Arif; Mahnoor Zahid; Samia Nawab; Malik Muhammad Qasim; Farhat Naseem Alvi; Sumbal Nazir; Ishrat Perveen; Naaz Abbas; Yasar Saleem; Sania Mazhar; et al. (Archives of Microbiology, 2024)

Predicting asphaltene adsorption on Fe3O4 nanoparticle using machine learning algorithms - Syed Imran Ali; Shaine Mohammadali Lalji; Usama Ahsan; Syed Muhammad Ali; Yassar Kamal Zia; Sajid Hussain; Muneeb Burney; Muhammad Qasim; Zeeshan Ahmad Arfeen (Arabian Journal of Geosciences, 2024)

Timing of India-Asia suturing: Evidence from a remnant peripheral foreland basin in Xigaze, South Tibet - Xu-Dong Guo; Lin Ding; Qiu-yun Guan; Deng Zeng; Chao Wang; Gui-zhen Guo; Hou-Qi Wang; Mei-Yu Liu; Xiang-Li Ding; Muhammad Qasim; Ya-Hui Yue; Jing Xie; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Sheep bone valorization: Enhancing gastronomic sustainability through hydroxyapatite-enriched potato wedges - Saba Liaqat; Zaheer Ahmed; Muhammad Usama Umer; Qasim Ali; Muhammad Farooq Mustafa; Ifra Ferheen; Muhammad Waseem (International Journal of Gastronomy and Food Science, 2024)

Advanced network pharmacology and molecular docking-based mechanism study to explore the multi-target pharmacological mechanism of Cymbopogon citratus against Alzheimer's disease - Kinza Fatima; Usman Ali Ashfaq; Muhammad Tahir ul Qamar; Muhammad Asif; Asma Haque; Muhammad Qasim; Mubarak A. Alamri; Ziyad Tariq Muhseen; Fatima Noor; Muhammad Sadaqat (South African Journal of Botany, 2024)

Alleviated lead toxicity in rice plant by co-augmented action of genome doubling and TiO2 nanoparticles on gene expression, cytological and physiological changes - Fozia Ghouri; Munazzam Jawad Shahid; Minghui Zhong; Muhammad Azam Zia; Sarah Owdah Alomrani; Jingwen Liu; Lixia Sun; Shafaqat Ali; Xiangdong Liu; Muhammad Qasim Shahid (Science of The Total Environment, 2024)

Revisiting the nexus between digital trade, green technological innovation, and environmental sustainability in BRICS economies - Han Yuerong; Muhammad Qasim Javaid; Muhammad Sibt e Ali; Muhammad Zada (Environmental Science and Pollution Research, 2024)

Modelling of debris-flow susceptibility and propagation: a case study from Northwest Himalaya - Hamza Daud; Javed Iqbal Tanoli; Sardar Muhammad Asif; Muhammad Qasim; Muhammad Ali; Junaid Khan; Zahid Imran Bhatti; Ishtiaq Ahmad Khan Jadoon (Journal of Mountain Science, 2024)

Atmospheric precursors from multiple satellites associated with the 2020 Mw 6.5 Idaho (USA) earthquake - Muhammad Qasim; Munawar Shah; Rasim Shahzad; Punyawi Jamjareegulgarn (Advances in Space Research, 2024)

Modulation of metal transporters, oxidative stress and cell abnormalities by synergistic application of silicon and titanium oxide nanoparticles: A strategy for cadmium tolerance in rice - Mingyu Lai; Fozia Ghouri; Samreen Sarwar; Sarah Owdah Alomrani; Muhammad Riaz; Fasih Ullah Haider; Jingwen Liu; Muhammad Imran; Shafaqat Ali; Xiangdong Liu; Muhammad Qasim Shahid (Chemosphere, 2023)

Fine mapping and candidate gene analysis of a major QTL for oil content in the seed of Brassica napus - Qing Zhao; Jian Wu; Lei Lan; Muhammad Shahid; Muhammad Uzair Qasim; Kaidi Yu; Chunyu Zhang; Chuchuan Fan; Yongming Zhou (Theoretical and Applied Genetics, 2023)

Elucidating the Mechanistic Role of Zinc-Lysine to Enhance Cd Tolerance in Diverse Wheat (Triticum aestivum L.) Cultivars Through Distinct Morpho-Physio-Biochemical Improvements Under Cd Stress - Muhammad Hussaan; Saghir Abbas; Qasim Ali; Muhammad Sohail Akram; Kashif Tanwir; Ahmad Raza; Sherjeel Hashmat; Muhammad Aqeel; Hassan Javed Chaudhary; Muhammad Tariq Javed (Journal of Soil Science and Plant Nutrition, 2023)

Field response and molecular screening of European wheat germplasm against powdery mildew at the Himalayan region of Pakistan - Aamir Iqbal; Zia Ur Rehman; Muhammad Rameez Khan; Amir Muhammad Khan; Shahid Ullah Khan; Muhammad Arif; Javaid Iqbal; Mujeeb Ur Rehman; Minhaj Ali; Muhammad Qasim; Imran Ali; Zakir Hussain Facho; et al. (Journal of Applied Genetics, 2023)

Systematic elucidation of the multi-target pharmacological mechanism of Terminalia arjuna against congestive cardiac failure via network pharmacology and molecular modelling approaches - Aqsa Asghar; Muhammad Qasim; Fatima Noor; Usman Ali Ashfaq; Muhammad Tahir ul Qamar; Muhammad Shareef Masoud; Rashid Bhatti; Ahmad Almatroudi; Faris Alrumaihi; Khaled S. Allemailem (Natural Product Research, 2023)

Design and numerical analysis of inverted well technique for aquifer recharge estimation - Muhammad Jahanzaib; Muhammad Kaleem Ullah; Muhammad Naveed Afridi; Muhammad Qasim (Groundwater for Sustainable Development, 2023)

Corrigendum to ‘Insights on the development of enhanced antifouling reverse osmosis membranes: Industrial applications and challenges’ [Desalination 553 (2023) 116460] - Muhammad Tawalbeh; Liyan Qalyoubi; Amani Al-Othman; Muhammad Qasim; Mohammad Mahdi A. Shirazi (Desalination, 2023)

Glutathione and zinc application upregulate the antioxidant system increasing photosynthetic pigments and growth under water stress in maize (Zea mays L.) - Farah Saeed; Abida Kausar; Qasim Ali; Athar Mahmood; Talha Javed; Rubab Shabbir; Muhammad Fraz Ali (Brazilian Journal of Botany, 2023)

Heavy metals in five commonly consumed fish species from River Swat, Pakistan, and their implications for human health using multiple risk assessment approaches - Kifayatullah Khan; Maria Zeb; Muhammad Younas; Hafiz Muhammad Adeel Sharif; Muhammad Yaseen; Abdullah G. Al-Sehemi; Yasar N. Kavil; Noor Samad Shah; Xianghui Cao; Afsheen Maryam; Muhammad Qasim (Marine Pollution Bulletin, 2023)

Molecular regulation of antioxidants and secondary metabolites act in conjunction to defend plants against pathogenic infection - Muhammad Usman Akbar; Muhammad Aqeel; Muhammad Shahzad Shah; Ghulam Jeelani; Naeem Iqbal; Ammara Latif; Rehab O. Elnour; Mohamed Hashem; Omar Mahmoud Alzoubi; Talaat Habeeb; Muhammad Qasim; Ali Noman (South African Journal of Botany, 2023)

Microplastics in soil differentially interfere with nutritional aspects of chilli peppers - Khadiga Alharbi; Muhammad Aqeel; Noreen Khalid; Atia Nazir; Muhammad Kashif Irshad; Fahad Mohammed Alzuaibr; Haifa AbdulAziz Sakit AlHaithloul; Noreen Akhter; Omar Mahmoud Al-Zoubi; Muhammad Qasim; Khalid M.Al Syaad; Manal Abdullah AlShaqhaa; et al. (South African Journal of Botany, 2023)

The protective role of tetraploidy and nanoparticles in arsenic-stressed rice: Evidence from RNA sequencing, ultrastructural and physiological studies - Fozia Ghouri; Munazzam Jawad Shahid; Jingwen Liu; Lixia Sun; Muhammad Riaz; Muhammad Imran; Shafaqat Ali; Xiangdong Liu; Muhammad Qasim Shahid (Journal of Hazardous Materials, 2023)

Correction: Ascorbic and Salicylic Acids Vitalized Growth, Biochemical Responses, Antioxidant Enzymes, Photosynthetic Efciency, and Ionic Regulation to Alleviate Salinity Stress in Sorghum bicolor - Muhammad Azeem; Robina Sultana; Athar Mahmood; Muhammad Qasim; Zamin Shaheed Siddiqui; Sahar Mumtaz; Talha Javed; Muhammad Umar; M. Yousuf Adnan; Manzer H. Siddiqui (Journal of Plant Growth Regulation, 2023)

Opening a new horizon in green HRM practices with big data analytics and its analogy to circular economy performance: an empirical evidence - Ka Yin Chau; Tian Huang; Massoud Moslehpour; Waqas Khan; Qasim Ali Nisar; Muhammad Haris (Environment, Development and Sustainability, 2023)

Exploring the relationships between attitudes toward emission trading schemes, artificial intelligence, climate entrepreneurship, and sustainable performance - Bin Hu; Shoaib Asim; Muhammad Sibt-e-Ali; Muhammad Qasim Javaid; Muhammad Ramzan (Environmental Science and Pollution Research, 2023)

Ascorbic and Salicylic Acids Vitalized Growth, Biochemical Responses, Antioxidant Enzymes, Photosynthetic Efficiency, and Ionic Regulation to Alleviate Salinity Stress in Sorghum bicolor - Muhammad Azeem; Robina Sultana; Athar Mahmood; Muhammad Qasim; Zamin Shaheed Siddiqui; Sahar Mumtaz; Talha Javed; Muhammad Umar; M. Yousuf Adnan; Manzer H. Siddiqui (Journal of Plant Growth Regulation, 2023)

How natural resources depletion, technological innovation, and globalization impact the environmental degradation in East and South Asian regions - Muhammad Sibt-e-Ali; Zhu Weimin; Muhammad Qasim Javaid; Muhammad Kamran Khan (Environmental Science and Pollution Research, 2023)

RETRACTED ARTICLE: Exploring the nonlinear relationship among financial development, human capital and CO2 emissions: a comparative study of South and East Asian emerging economies - Muhammad Qasim Javaid; Kong Ximei; Muhammad Irfan; Muhammad Sibt-e-Ali; Tanzeela Shams (Environmental Science and Pollution Research, 2023)

Evaluation of phytoremediation potential and resistance of Gladiolus grandiflora L. against cadmium stress - Syed Ali Qasim Bukhari; Aamir Nawaz; Muhammad Dawood (Environmental Geochemistry and Health, 2023)

Segmentation of digital rock images using texture analysis and deep network - Shahzad Manzoor; Tehreem Qasim; Naeem Bhatti; Muhammad Zia (Arabian Journal of Geosciences, 2023)

A graft that crafts nontransgenic and genome-edited plants - Muhammad Jawad Akbar Awan; Muhammad Qasim Aslam; Rubab Zahra Naqvi; Imran Amin; Shahid Mansoor (Trends in Plant Science, 2023)

From COVID to conflict: Understanding the deriving forces of environment and implications for natural resources - Qasim Raza Khan; Mao Xinshu; Ghulam Muhammad Qamri; Ahmad Nawaz (Resources Policy, 2023)

Insights on the development of enhanced antifouling reverse osmosis membranes: Industrial applications and challenges - Muhammad Tawalbeh; Liyan Qalyoubi; Amani Al-Othman; Muhammad Qasim; Mohammad Shirazi (Desalination, 2023)

High prevalence of extensively drug resistant and extended spectrum beta lactamases (ESBLs) producing uropathogenic Escherichia coli isolated from Faisalabad, Pakistan - Beenish Ehsan; Asma Haque; Muhammad Qasim; Aamir Ali; Yasra Sarwar (World Journal of Microbiology and Biotechnology, 2023)

Novel plasmids in multidrug-resistant Shigella flexneri serotypes from Pakistan - Iqbal Nisa; Arnold Driessen; Jeroen Nijland; Hazir Rahman; Jochen Mattner; Muhammad Qasim (Archives of Microbiology, 2023)

Polyploidy and zinc oxide nanoparticles alleviated Cd toxicity in rice by modulating oxidative stress and expression levels of sucrose and metal-transporter genes - Fozia Ghouri; Munazzam Jawad Shahid; Jingwen Liu; Mingyu Lai; Lixia Sun; Jinwen Wu; Xiangdong Liu; Shafaqat Ali; Muhammad Qasim Shahid (Journal of Hazardous Materials, 2023)

Production planning approaches: a review from green perspective - Muhammad Qasim; Kuan Yew Wong; Mohd Syahril Ramadhan Mohd Saufi (Environmental Science and Pollution Research, 2023)

Corrigendum to ‘Prediction of carbon-dioxide activity coefficient for solubility in ionic liquids using multi-non-linear regression analysis’, Chemosphere, 311, (2023), 1–10, 137102 - Sami-ullah Rather; Azmi M. Shariff; Aliyu Adebayo Sulaimon; Hisham S. Bamufleh; Ali Qasim; Muhammad Saad Khan; Hesham Alhumade; Usman Saeed; Walid M. Alalayah (Chemosphere, 2023)

In-situ construction of binder-free MnO2/MnSe heterostructure membrane for high-performance energy storage in pseudocapacitors - Qasim Abbas; Abdul Mateen; Sajid Hussain Siyal; Najam Ul Hassan; Asma A. Alothman; Mohamed Ouladsmane; Sayed M. Eldin; Mohd Zahid Ansari; Muhammad Sufyan Javed (Chemosphere, 2023)

Prediction of carbon-dioxide activity coefficient for solubility in ionic liquids using multi-non-linear regression analysis. - Sami-ullah Rather; Azmi M. Shariff; Aliyu Adebayo Sulaimon; Hisham S. Bamufleh; Ali Qasim; Muhammad Saad Khan; Hesham Alhumade; Usman Saeed; Walid M. Alalayah (Chemosphere, 2023)

Spatial and temporal analyses of land use changes with special focus on seasonal variation in snow cover in District Chitral; a Hindu Kush mountain region of Pakistan - Muhammad Qasim; Mudassir Khan; Wajid Rashid (Remote Sensing Applications: Society and Environment, 2023)

Free Swimming and Exercise-Induced Pulmonary Hemorrhage in Endurance Horses: A Preliminary Study - Tatiana Vinardell; Florent David; Angelica M. Galezowski; Mohammad Ali; Muhammad Qasim; Shannon L. Massie; Persephone McCrae; Silvio Filho; Renaud Leguillette (Journal of Equine Veterinary Science, 2023)

Genome mining, antimicrobial and plant growth-promoting potentials of halotolerant Bacillus paralicheniformis ES-1 isolated from salt mine - Sajid Iqbal; Muhammad Qasim; Hazir Rahman; Naeem Khan; Rehan Zafar Paracha; Muhammad Faraz Bhatti; Aneela Javed; Hussnain Ahmed Janjua (Molecular Genetics and Genomics, 2023)

Screening, Characterization and Optimization of Bioactive Peptides with Antibacterial Activities Against Multi-Drug Resistant Pathogens, Produced by Bacillus safensis Strain MK-12.1 - Sajid Iqbal; Farida Begum; Muhammad Qasim (International Journal of Peptide Research and Therapeutics, 2022)

Tanneries impact on groundwater quality: a case study of Kasur city in Pakistan - Hafiz Qasim Ali; Muhammad Umair Yasir; Amir Farooq; Mahrukh Khan; Muhammad Salman; Muhammad Waqar (Environmental Monitoring and Assessment, 2022)

Deciphering distinct root exudation, ionomics, and physio-biochemical attributes of Serratia marcescens CP-13 inoculated differentially Cd tolerant Zea mays cultivars - Kashif Tanwir; Muhammad Shahid; Saghir Abbas; Qasim Ali; Muhammad Sohail Akram; Hassan Javed Chaudhary; Muhammad Tariq Javed (Environmental Science and Pollution Research, 2022)

Potential of Fish Scale Biochar Nanocomposite with ZnO for Effective Sequestration of Cr (VI) from Water: Modeling and Kinetics - Azhar Ul Islam; Muhammad Mohsin Iqbal; Muhammad Imran; Muhammad Adnan Tariq; Muhammad Nadeem; Muhammad Qasim Kakar; Muhammad Nawaz; Muhammad Amjad; Saeed Ahmad Qaisrani; Muhammad Rizwan; Shafaqat Ali (International Journal of Environmental Research, 2022)

Comparative low lethal effects of three insecticides on demographical traits and enzyme activity of the Spodoptera exigua (Hübner) - Muhammad Hafeez; Farman Ullah; Muhammad Musa Khan; Zhangqian Wang; Hina Gul; Xiaowei Li; Jun Huang; Junaid Ali Siddiqui; Muhammad Qasim; Rui-Long Wang; Muhammad Imran; Mohammed A. Assiri; et al. (Environmental Science and Pollution Research, 2022)

Geology and petrogenesis of gabbro from the Zhob Ophiolite, Balochistan, Pakistan - Abdul Naeem; Muhammad Ishaq Kakar; Rehanul Haq Siddiqui; Andrew C. Kerr; Muhammad Qasim Jan; Muhammad Ayoub Khan (Arabian Journal of Geosciences, 2022)

A Comparative Analysis of Adopters and Non‐adopters of Drip Irrigation under Plastic Tunnels for Cucumber ( Cucumis sativus L.) Production in Balochistan, Pakistan - Said Qasim; Muhammad Qasim; Anees Hassan; Ghulam Murtaza; Amir Nawaz Khan (Irrigation and Drainage, 2022)
This research tries to compare the water use efficiency, electricity efficiency and economic efficiency of adopters and non‐adopters of drip irrigation under plastic tunnels (DIUPT). Data regarding the socio‐economic conditions of farmers and their views on the advantages and disadvantages of the DIUPT were collected through a questionnaire survey of 200 farmers. For expenses, income, electricity efficiency and water use efficiency, we collected data only from the sample farmers, i.e. one adopter and one non‐adopter. Results also revealed that the total horsepower (HP) hours of water per acre used for drip‐irrigated cucumber under plastic tunnels was 240 compared to 576 HP hours for the flood method of irrigation, thereby saving 58% (336 HP hours) of energy. In other words, with the same amount of water used for irrigating 1 acre of cucumber under flood irrigation, 2.4 acres of cucumber could be irrigated using drip irrigation. Realizing about 51% higher yields under drip irrigation, adopters enjoy 40% higher returns than non‐adopter farmers. The study recommends dissemination of information to farmers about DIUPT through training and seminars. Adoption of these technologies would lead to efficient and sustainable use of already depleting water resources in the drought‐prone province of Balochistan.

An overview of sucrose transporter (SUT) genes family in rice - Lixia Sun; Ruilian Deng; Jingwen Liu; Mingyu Lai; Jinwen Wu; Xiangdong Liu; Muhammad Qasim Shahid (Molecular Biology Reports, 2022)

A review of the global climate change impacts, adaptation, and sustainable mitigation measures - Kashif Abbass; Muhammad Zeeshan Qasim; Huaming Song; Muntasir Murshed; Haider Mahmood; Ijaz Younis (Environmental Science and Pollution Research, 2022)

Do geopolitical risk and energy consumption contribute to environmental degradation? Evidence from E7 countries - Muhammad Iftikhar ul Husnain; Qasim Raza Syed; Arooj Bashir; Muhammad Aamir Khan (Environmental Science and Pollution Research, 2022)

Ionic liquids for the inhibition of gas hydrates. A review - Ihtisham Ul Haq; Ali Qasim; Bhajan Lal; Dzulkarnain B. Zaini; Khor Siak Foo; Muhammad Mubashir; Kuan Shiong Khoo; Dai-Viet N. Vo; Eric Leroy; Pau Loke Show (Environmental Chemistry Letters, 2022)

3-Dimensional membrane capsules: Synthesis modulations for the remediation of environmental pollutants – A critical review - Imran Ali; Juying Li; Changsheng Peng; Muhammad Qasim; Zahid M. Khan; Iffat Naz; Muhammad Sultan; Muhammad Rauf; Waheed Iqbal; Hafiz Muhammad Adeel Sharif (Critical Reviews in Environmental Science and Technology, 2022)

Baseline toxicity of ten insecticides from organophosphate, pyrethroid and novel mode of action groups against Droschica mangiferae (Homoptera: Margarodidae) collected from citrus orchard in 2017–19 - Muhammad Nawaz Khan; Muhammad Babar Shahzad Afzal; Naima Din; Afifa Naeem; Ansa Banazeer; Malik Abdul Rehman; Hira Tariq; Muhammad Raza Salik; Muhammad Qasim (International Journal of Tropical Insect Science, 2022)

Sarcococca saligna extract attenuates formaldehyde-induced arthritis in Wistar rats via modulation of pro-inflammatory and inflammatory biomarkers - Maryam Farrukh; Uzma Saleem; Muhammad Qasim; Maria Manan; Muhammad Ajmal Shah (Inflammopharmacology, 2022)

Antimicrobial Resistance of Shigella flexneri in Pakistani Pediatric Population Reveals an Increased Trend of Third-Generation Cephalosporin Resistance - Iqbal Nisa; Mohammad Haroon; Arnold Driessen; Jeroen Nijland; Hazir Rahman; Nusrat Yasin; Mubashir Hussain; Taj Ali Khan; Amjad Ali; Saeed Ahmad Khan; Muhammad Qasim (Current Microbiology, 2022)

Silencing of Curlin Protein via M13 Phagemid-Mediated Synthetic sRNA Expression Reduces Virulence in the Avian Pathogenic E. coli (APEC) - Sayed Abdullah; Quratul Ain; Amna Jalil; Dilawar Khan; Arsalan Khan; Muhammad Qasim; Malik Badshah; Fazal Adnan (Current Microbiology, 2022)

Integration of multispectral and hyperspectral remote sensing data for lithological mapping in Zhob Ophiolite, Western Pakistan - Muhammad Qasim; Shuhab D. Khan; Rashid Haider; Mehboob ur Rasheed (Arabian Journal of Geosciences, 2022)

Humic acid overcomes salinity barriers and stimulates growth of Urochondra setulosa by altering ion-flux and photochemistry - Sonia Bano; Muhammad Zaheer Ahmed; Zainul Abideen; Muhammad Qasim; Bilquees Gul; Nasir Uddin Khan (Acta Physiologiae Plantarum, 2022)

Greening the workforce in higher educational institutions: The pursuance of environmental performance - Qazi Muhammad Ali; Qasim Ali Nisar; Rana Zain ul Abidin; Rabia Qammar; Kashif Abbass (Environmental Science and Pollution Research, 2022)

Climate change impact uncertainty assessment and adaptations for sustainable maize production using multi-crop and climate models - Mubashra Yasin; Ashfaq Ahmad; Tasneem Khaliq; Muhammad Habib-ur-Rahman; Salma Niaz; Thomas Gaiser; Iqra Ghafoor; Hafiz Suboor ul Hassan; Muhammad Qasim; Gerrit Hoogenboom (Environmental Science and Pollution Research, 2022)
Future climate scenarios are predicting considerable threats to sustainable maize production in arid and semi-arid regions. These adverse impacts can be minimized by adopting modern agricultural tools to assess and develop successful adaptation practices. A multi-model approach (climate and crop) was used to assess the impacts and uncertainties of climate change on maize crop. An extensive field study was conducted to explore the temporal thermal variations on maize hybrids grown at farmer’s fields for ten sowing dates during two consecutive growing years. Data about phenology, morphology, biomass development, and yield were recorded by adopting standard procedures and protocols. The CSM-CERES, APSIM, and CSM-IXIM-Maize models were calibrated and evaluated. Five GCMs among 29 were selected based on classification into different groups and uncertainty to predict climatic changes in the future. The results predicted that there would be a rise in temperature (1.57–3.29 °C) during the maize growing season in five General Circulation Models (GCMs) by using RCP 8.5 scenarios for the mid-century (2040–2069) as compared with the baseline (1980–2015). The CERES-Maize and APSIM-Maize model showed lower root mean square error values (2.78 and 5.41), higher d -index (0.85 and 0.87) along reliable R 2 (0.89 and 0.89), respectively for days to anthesis and maturity, while the CSM-IXIM-Maize model performed well for growth parameters (leaf area index, total dry matter) and yield with reasonably good statistical indices. The CSM-IXIM-Maize model performed well for all hybrids during both years whereas climate models, NorESM1-M and IPSL-CM5A-MR, showed less uncertain results for climate change impacts. Maize models along GCMs predicted a reduction in yield (8–55%) than baseline. Maize crop may face a high yield decline that could be overcome by modifying the sowing dates and fertilizer (fertigation) and heat and drought-tolerant hybrids.

The genetic drivers for the successful invasive potential of a generalist bird, the House crow - Farheena Iqbal; Urszula Krzeminska-Ahmadzai; Qasim Ayub; Robyn Wilson; Beng Kah Song; Muhammad Fahim; Sadequr Rahman (Biological Invasions, 2022)

Assessing diversity of aphids (Hemiptera: Aphididae) along elevation gradient in Azad Jammu and Kashmir-Pakistan - Muhammad Amin; Khalid Mahmood; Imran Bodlah; Muhammad Qasim (International Journal of Tropical Insect Science, 2022)

Intron-containing hairpin RNA interference vector for OBP8 show promising mortality in peach potato aphid - Amber Afroz; Safeena Aslam; Umer Rashid; Muhammad Faheem Malik; Nadia Zeeshan; Muhammad Ramzan Khan; Muhammad Qasim Shahzad But; Sabaz Ali Khan (Plant Cell, Tissue and Organ Culture (PCTOC), 2022)

Seed Priming with Sodium Nitroprusside and H2O2 Confers Better Yield in Wheat Under Salinity: Water Relations, Antioxidative Defense Mechanism and Ion Homeostasis - Noman Habib; Qasim Ali; Shafaqat Ali; Muhammad Zulqarnain Haider; Muhammad Tariq Javed; Mubashra Khalid; Rashida Perveen; Abdulaziz Abdullah Alsahli; Mohammed Nasser Alyemeni (Journal of Plant Growth Regulation, 2021)

Implementation of Vaccinomics and In-Silico Approaches to Construct Multimeric Based Vaccine Against Ovarian Cancer - Muhammad Sufyan; Farah Shahid; Faiza Irshad; Anam Javaid; Muhammad Qasim; Usman Ali Ashfaq (International Journal of Peptide Research and Therapeutics, 2021)

Tick-borne Diseases in Sheep and Goats in Pakistan: A Systematic Review and Meta-analysis - Aqsa Mushtaq; Tehniat Shoukat; Tanzila Mumtaz; Muhammad Qasim; Kiran Ajmal; Nayab Fatima; Aisha Khan; Misbah Kouser; Nazeer Hussain; Sadia Selim Khan; Mohammed Sohail Afzal; Sami Simsek; et al. (Acta Parasitologica, 2021)

Environmental impact and diversity of protease-producing bacteria in areas of leather tannery effluents of Sialkot, Pakistan - Muhammad Qasim Butt; Nadia Zeeshan; Naeem Mahmood Ashraf; Muhammad Aftab Akhtar; Hina Ashraf; Amber Afroz; Aqsa Shaheen; Shumaila Naz (Environmental Science and Pollution Research, 2021)

Exploring a new perspective of sustainable development drive through environmental Phillips curve in the case of the BRICST countries - Muhammad Khalid Anser; Nicholas Apergis; Qasim Raza Syed; Andrew Adewale Alola (Environmental Science and Pollution Research, 2021)

Does geopolitical risk escalate CO2 emissions? Evidence from the BRICS countries - Muhammad Khalid Anser; Qasim Raza Syed; Nicholas Apergis (Environmental Science and Pollution Research, 2021)

Sedimentary evolution of middle Jurassic epeiric carbonate ramp Hazara Basin Lesser Himalaya Pakistan - Malik Muhammad Saud Sajid Khan; Qasim Ali Jadoon; Muhammad Umar; Ahsan Ali Khan (Carbonates and Evaporites, 2021)

A review of landslides related to the 2005 Kashmir Earthquake: implication and future challenges - Muhammad Basharat; Muhammad Tayyib Riaz; M. Qasim Jan; Chong Xu; Saima Riaz (Natural Hazards, 2021)

Statistical analysis and temporal trend of annual maximum temperature with teleconnection patterns of different stations in Pakistan - Tasir Khan; Yejuan Wang; Naiming Yuan; Abdullah; Muhammad Salam; Fakhri Alam; Qasim Shah (Arabian Journal of Geosciences, 2021)

RP-HPLC-based phytochemical analysis and diverse pharmacological evaluation of Quercus floribunda Lindl. ex A. Camus nuts extracts - Madiha Ahmed; Muhammad Adil; Ihsan-ul- Haq; Muhammad Khalid Tipu; Muhammad Qasim; Bilquees Gul (Natural Product Research, 2021)

Re-evaluating the asymmetric conventional energy and renewable energy consumption-economic growth nexus for Pakistan - Muhammad Afaq Haider Jafri; Huizheng Liu; Ahmed Usman; Qasim Raza Khan (Environmental Science and Pollution Research, 2021)

Epidemiology of molecular probes in Xpert MTB/RIF assay in Khyber Pakhtunkhwa, Pakistan - Anwar Sheed Khan; Muhammad Tahir Khan; Sajid Ali; Taj Ali Khan; Muhammad Qasim; Arif Malik; Sajid Ali; Wasim Sajjad; Qurrat ul ain; Muhammad Irfan (Archives of Microbiology, 2021)

Phyto-derivatives: an efficient eco-friendly way to manage Trogoderma granarium (Everts) (Coleoptera: Dermestidae) - Waqar Islam; Ali Noman; Komivi Senyo Akutse; Muhammad Qasim; Habib Ali; Ijaz Haider; Mohamed Hashem; Saad Alamri; Omar Mahmoud al Zoubi; Khalid Ali Khan (International Journal of Tropical Insect Science, 2021)

Impact of economic policy uncertainty on CO2 emissions: evidence from top ten carbon emitter countries - Muhammad Khalid Anser; Nicholas Apergis; Qasim Raza Syed (Environmental Science and Pollution Research, 2021)

Monitoring of heavy metal pollution in urban and rural environments across Pakistan using House crows (Corvus splendens) as bioindicator - Farheena Iqbal; Qasim Ayub; Robyn Wilson; Beng Kah Song; Amin Talei; Keng Yoon Yeong; Andreas Aditya Hermawan; Muhammad Fahim; Sadequr Rahman (Environmental Monitoring and Assessment, 2021)

Screening of different legumes for the developmental preference of Callosobruchus maculatus (Bruchidae: Coleoptera) - Muhammad Shahid Nisar; Ikram Ul Haq; Hassan Ramzan; Dalal M. Aljedani; Muhammad Qasim; Waqar Islam; Khalid Ali Khan (International Journal of Tropical Insect Science, 2021)

Comparative pathogenicity of four entomopathogenic fungal species against nymphs and adults of citrus red mite on the citrus plantation - Muhammad Qasim; Jiang Ronliang; Waqar Islam; Habib Ali; Khalid Ali Khan; Chandra Kanta Dash; Zakia A. Jamal; Liande Wang (International Journal of Tropical Insect Science, 2021)

Elucidating Cd-mediated distinct rhizospheric and in planta ionomic and physio-biochemical responses of two contrasting Zea mays L. cultivars - Saghir Abbas; Muhammad Tariq Javed; Qasim Ali; Muhammad Sohail Akram; Kashif Tanwir; Shafaqat Ali; Hassan Javed Chaudhary; Naeem Iqbal (Physiology and Molecular Biology of Plants, 2021)

Artemisia chamaemelifolia Vill: a rare species of genus Artemisia (Asteraceae-Anthemideae) now present in the northeast (Gilgit-Baltistan) region of Pakistan - Adil Hussain; Muhammad Qasim Hayat; Syed Ali Imran Bokhari (Biologia, 2021)

Identification and computational analysis of USH1C, and SLC26A4 variants in Pakistani families with prelingual hearing loss - Muhammad Noman; Shazia A. Bukhari; Sakina Rehman; Muhammad Qasim; Muhammad Ali; Saima Riazuddin; Zubair M. Ahmed (Molecular Biology Reports, 2020)

De Novo Assembly and Annotation of the Juvenile Tuber Transcriptome of a Gastrodia elata Hybrid by RNA Sequencing: Detection of SSR Markers - Yunsheng Wang; Muhammad Qasim Shahid; Fozia Ghouri; Faheem Shehzad Baloch (Biochemical Genetics, 2020)

Reproductive tissues-specific meta-QTLs and candidate genes for development of heat-tolerant rice cultivars - Qasim Raza; Awais Riaz; Khurram Bashir; Muhammad Sabar (Plant Molecular Biology, 2020)

An indicator based approach for assessing household’s perceptions of landslide risk in Murree hills of Pakistan - Said Qasim; Muhammad Qasim (Natural Hazards, 2020)

Biological and phytochemical studies on Capparis decidua (Forssk) Edgew from Cholistan desert - Shazia Anjum; Muhammad Asif; Kashaf Zia; Bakhat Jahan; Muhammad Ashraf; Shafqat Hussain; Muhammad Qasim Hayat; Muhammad Raza Shah; Muhammad Nawaz Tahir (Natural Product Research, 2020)

Correction to: Appraisal of disease-modifying potential of amlodipine as an anti-arthritic agent: new indication for an old drug - Sumera Qasim; Alamgeer; Saima Kalsoom; Muhammad Shahzad; Hafiz Muhammad Irfan; Muhammad Shoaib Zafar; Ishfaq Ali Bukhari; Fahim Vohra; Sibtain Afzal (Inflammopharmacology, 2020)

Appraisal of disease-modifying potential of amlodipine as an anti-arthritic agent: new indication for an old drug - Sumera Qasim; Alamgeer; Saima Kalsoom; Muhammad Shahzad; Hafiz Muhammad Irfan; Muhammad Shoaib Zafar; Ishfaq Ali Bukhari; Fahim Vohra; Sibtain Afzal (Inflammopharmacology, 2020)

Molecular epidemiology of Shigella flexneri isolated from pediatrics in a diarrhea-endemic area of Khyber Pakhtunkhwa, Pakistan - Iqbal Nisa; Muhammad Qasim; Arnold Driessen; Jeroen Nijland; Fazli Bari; Mohammad Haroon; Hazir Rahman; Nusrat Yasin; Taj Ali Khan; Mubbashir Hussain; Waheed Ullah (European Journal of Clinical Microbiology & Infectious Diseases, 2020)

Shigella flexneri: an emerging pathogen - Iqbal Nisa; Muhammad Qasim; Nusrat Yasin; Rafi Ullah; Anwar Ali (Folia Microbiologica, 2020)

Lipids as biomarkers of brain disorders - Ghulam Hussain; Haseeb Anwar; Azhar Rasul; Ali Imran; Muhammad Qasim; Shamaila Zafar; Muhammad Imran; Syed Kashif Shahid Kamran; Nimra Aziz; Aroona Razzaq; Waseem Ahmad; Asghar Shabbir; et al. (Critical Reviews in Food Science and Nutrition, 2020)

The potential applications of picotechnology in biomedical and environmental sciences - Muhammad Zeeshan Qasim; Hafiz Mohkum Hammad; Farhat Abbas; Shafqat Saeed; Hafiz Faiq Bakhat; Wajid Nasim; Wajid Farhad; Faiz Rabbani; Shah Fahad (Environmental Science and Pollution Research, 2020)

In vitro induction of auto-allotetraploid in a newly developed wild rice line from Oryza alta Swallen - Liusheng Zhang; Fimanekeni Ndaitavela Shivute; Muhammad Qasim Shahid; Nabieu Kamara; Jinwen Wu; Xiangdong Liu (Plant Cell, Tissue and Organ Culture (PCTOC), 2019)

Phytotoxic analysis of coastal medicinal plants and quantification of phenolic compounds using HPLC - Muhammad Qasim; Yoshiharu Fujii; Muhammad Zaheer Ahmed; Irfan Aziz; Kazuo N. Watanabe; M. Ajmal Khan (Plant Biosystems, 2019)

The effect of lead pollution on nutrient solution pH and concomitant changes in plant physiology of two contrasting Solanum melongena L. cultivars - Muhammad Tariq Javed; Noman Habib; Muhammad Sohail Akram; Qasim Ali; Muhammad Zulqurnain Haider; Kashif Tanwir; Asia Shauket; Hassan Javed Chaudhary (Environmental Science and Pollution Research, 2019)

Identification of two further agriculturally important begomoviruses and their associated satellites infecting the weed Digera arvensis in Pakistan - Afzal Akram; Khalid Pervaiz Akhtar; Najeeb Ullah; Muhammad Qasim Aslam; Peter Moffett; Shahid Mansoor; Rob W. Briddon; Muhammad Saeed (European Journal of Plant Pathology, 2019)

Physiological and biochemical attributes of bread wheat (Triticum aestivum L.) seedlings are influenced by foliar application of silicon and selenium under water deficit - Abdul Sattar; Mumtaz Akhtar Cheema; Ahmad Sher; Muhammad Ijaz; Sami Ul-Allah; Ahmad Nawaz; Tahira Abbas; Qasim Ali (Acta Physiologiae Plantarum, 2019)

Sub-lethal effects of lufenuron exposure on spotted bollworm Earias vittella (Fab): key biological traits and detoxification enzymes activity - Muhammad Hafeez; Saad Jan; Muhammad Nawaz; Ehsan Ali; Bahar Ali; Muhammad Qasim; G. Mandela Fernández-Grandon; Muhammad Shahid; Mo Wang (Environmental Science and Pollution Research, 2019)

Seed priming with silicon nanoparticles improved the biomass and yield while reduced the oxidative stress and cadmium concentration in wheat grains - Afzal Hussain; Muhammad Rizwan; Qasim Ali; Shafaqat Ali (Environmental Science and Pollution Research, 2019)

Characteristics of pipe corrosion scales in untreated water distribution system and effect on water quality in Peshawar, Pakistan - Dilawar Farhan Shams; Saeed Islam; Baoyou Shi; Waliullah Khan; Buddhika Gunawardana; Maryam Saad; Muhammad Qasim; Haider Ali Javed; Sahib Gul Afridi; Muhammad Naeem; Gul Shahzada Khan (Environmental Science and Pollution Research, 2019)

Extraction optimization, total phenolic, flavonoid contents, HPLC-DAD analysis and diverse pharmacological evaluations of Dysphania ambrosioides (L.) Mosyakin & Clemants - Tanzeel Zohra; Muhammad Ovais; Ali Talha Khalil; Muhammad Qasim; Muhammad Ayaz; Zabta Khan Shinwari (Natural Product Research, 2019)

Cytological and transcriptome analyses reveal abrupt gene expression for meiosis and saccharide metabolisms that associated with pollen abortion in autotetraploid rice - Lin Chen; Muhammad Qasim Shahid; Jinwen Wu; Zhixiong Chen; Lan Wang; Xiangdong Liu (Molecular Genetics and Genomics, 2018)

Regolith thickness modeling using a GIS approach for landslide distribution analysis, NW Himalayas - Muhammad Basharat; Masood Qasim; Muhammad Shafique; Nasir Hameed; Muhammad Tayyib Riaz; Muhammad Rustam Khan (Journal of Mountain Science, 2018)

Correction to: Genome-Wide Analysis of Genetic Variations and the Detection of Rich Variants of NBS-LRR Encoding Genes in Common Wild Rice Lines - Hang Yu; Muhammad Qasim Shahid; Rongbai Li; Wei Li; Wen Liu; Fozia Ghouri; Xiangdong Liu (Plant Molecular Biology Reporter, 2018)

Genome-Wide Analysis of Genetic Variations and the Detection of Rich Variants of NBS-LRR Encoding Genes in Common Wild Rice Lines - Hang Yu; Muhammad Qasim Shahid; Rongbai Li; Wei Li; Wen Liu; Fozia Ghouri; Xiangdong Liu (Plant Molecular Biology Reporter, 2018)

Experimental investigations on a diesel engine operated with fuel blends derived from a mixture of Pakistani waste tyre oil and waste soybean oil biodiesel - Muhammad Qasim; Tariq Mahmood Ansari; Mazhar Hussain (Environmental Science and Pollution Research, 2018)

Effects of anthropogenic nitrogen deposition on soil nitrogen mineralization and immobilization in grassland soil under semiarid climatic conditions - Ambreen Bhatti; Jawad Ahmad; Muhammad Qasim; Muhammad Riaz; Malcolm S. Cresser (Environmental Monitoring and Assessment, 2018)

Prevalence of selected pharmaceuticals in surface water receiving untreated sewage in northwest Pakistan - Aisha Khan; Dilawar Farhan Shams; Waliullah Khan; Aamir Ijaz; Muhammad Qasim; Maryam Saad; Ayesha Hafeez; Shams Ali Baig; Nisar Ahmed (Environmental Monitoring and Assessment, 2018)

Sugar beet extract acts as a natural bio-stimulant for physio-biochemical attributes in water stressed wheat (Triticum aestivum L.) - Ali Noman; Qasim Ali; Jazia Naseem; M. Tariq Javed; Hina Kanwal; Waqar Islam; Muhammad Aqeel; Noreen Khalid; Sara Zafar; Muhammad Tayyeb; Naeem Iqbal; Mahmooda Buriro; et al. (Acta Physiologiae Plantarum, 2018)

A novel mutation in RDH5 gene causes retinitis pigmentosa in consanguineous Pakistani family - Neelam Sultan; Irfan Ali; Shazia Anwer Bukhari; Shahid Mahmood Baig; Muhammad Asif; Muhammad Qasim; Muhammad Imran Naseer; Mahmood Rasool (Genes & Genomics, 2018)

Deciphering the growth, organic acid exudations, and ionic homeostasis of Amaranthus viridis L. and Portulaca oleracea L. under lead chloride stress - Muhammad Tariq Javed; Muhammad Sohail Akram; Noman Habib; Kashif Tanwir; Qasim Ali; Nabeel Khan Niazi; Huma Gul; Naeem Iqbal (Environmental Science and Pollution Research, 2018)

Association of chili leaf curl betasatellite with tomato leaf curl disease - Muhammad Qasim Aslam; Khalid P. Akhtar; Mohy-u-Din Akram; Muhammad Y. Saleem; Nighat Sarwar; Sumaira Yousaf (Journal of General Plant Pathology, 2017)

Effects of different temperature regimes on survival of Diaphorina citri and its endosymbiotic bacterial communities - Mubasher Hussain; Komivi Senyo Akutse; Keppanan Ravindran; Yongwen Lin; Bamisope Steve Bamisile; Muhammad Qasim; Chandra Kanta Dash; Liande Wang (Environmental Microbiology, 2017)
The Asian citrus psyllid, Diaphorina citri , is a major pest of citrus and vector of citrus greening (huanglongbing) in Asian. In our field‐collected psyllid samples, we discovered that Fuzhou (China) and Faisalabad (Pakistan), populations harbored an obligate primary endosymbiont Candidatus Carsonella (gen. nov.) with a single species, Candidatus Carsonella ruddii (sp. nov.) and a secondary endosymbiont, Wolbachia surface proteins (WSP) which are intracellular endosymbionts residing in the bacteriomes. Responses of these symbionts to different temperatures were examined and their host survival assessed. Diagnostic PCR assays showed that the endosymbionts infection rates were not significantly reduced in both D. citri populations after 24 h exposure to cold or heat treatments. Although quantitative PCR assays showed significant reduction of WSP relative densities at 40°C for 24 h, a substantial decrease occurred as the exposure duration increased beyond 3 days. Under the same temperature regimes, Ca. C. ruddii density was initially less affected during the first exposure day, but rapidly reduced at 3–5 days compared to WSP. However, the mortality of the psyllids increased rapidly as exposure time to heat treatment increased. The responses of the two symbionts to unfavorable temperature regimes highlight the complex host‐symbionts interactions between D. citri and its associated endosymbionts.

RNA-Seq reveals differential expression patterns of genes associated with carotenoid accumulation in loquat - Ting-ting Zheng; Zhi-ke Zhang; Muhammad Qasim Shahid; Wei-ling Wei; Faheem Shehzad Baloch; Jin-cheng Wu; Shun-quan Lin; Xiang-hui Yang (Acta Physiologiae Plantarum, 2017)

Felsic dykes in the Neoproterozoic Nagar Parkar Igneous Complex, SE Sindh, Pakistan: geochemistry and tectonic settings - Tahseenullah Khan; Mamoru Murata; M. Qasim Jan; Hafiz Ur Rehman; Muhammad Zafar; Hiroaki Ozawa; Anwar Qadir; Saqib Mehmood (Arabian Journal of Geosciences, 2017)

Processes of initial collision and suturing between India and Asia - Lin Ding; Satybaev Maksatbek; FuLong Cai; HouQi Wang; PeiPing Song; WeiQiang Ji; Qiang Xu; LiYun Zhang; Qasim Muhammad; Baral Upendra (Science China Earth Sciences, 2017)

Assessment of tap water quality and corrosion scales from the selected distribution systems in northern Pakistan - Shams Ali Baig; Zimo Lou; Muzaffar Ali Baig; Muhammad Qasim; Dilawar Farhan Shams; Qaisar Mahmood; Xinhua Xu (Environmental Monitoring and Assessment, 2017)

Drought tolerance potential of Vigna mungo L. lines as deciphered by modulated growth, antioxidant defense, and nutrient acquisition patterns - Qasim Ali; Muhammad Zulqurnain Haider; Wasif Iftikhar; Sidra Jamil; M. Tariq Javed; Ali Noman; Muhammad Iqbal; Rashida Perveen (Brazilian Journal of Botany, 2016)

Molecular characterization and growth optimization of halo-tolerant protease producing Bacillus Subtilis Strain BLK-1.5 isolated from salt mines of Karak, Pakistan - Nawab Ali; Nimat Ullah; Muhammad Qasim; Hazir Rahman; Shahid Niaz Khan; Abdul Sadiq; Muhammad Adnan (Extremophiles, 2016)

Cofilin as a Promising Therapeutic Target for Ischemic and Hemorrhagic Stroke - Qasim Alhadidi; Muhammad Shahdaat Bin Sayeed; Zahoor A. Shah (Translational Stroke Research, 2016)

Copper-resistant bacteria reduces oxidative stress and uptake of copper in lentil plants: potential for bacterial bioremediation - Faisal Islam; Tahira Yasmeen; Qasim Ali; Muhammad Mubin; Shafaqat Ali; Muhammad Saleem Arif; Sabir Hussain; Muhammad Riaz; Farhat Abbas (Environmental Science and Pollution Research, 2016)

Stratigraphic characterization and structural analysis of the northwestern Hazara Ranges across Panjal Thrust, northern Pakistan - Muhammad Qasim; Muhammad Asif Khan; Muhammad Haneef (Arabian Journal of Geosciences, 2015)

Geochemistry and petrogenesis of Oligocene volcaniclastic rocks from the Chagai arc: implications for the emplacement of porphyry copper deposits - Rehanul Haq Siddiqui; Muhammad Asif Khan; Muhammad Qasim Jan; Mohammad Ishaq Kakar; Andrew C. Kerr (Arabian Journal of Geosciences, 2015)

Modulations in plant water relations and tissue-specific osmoregulation by foliar-applied ascorbic acid and the induction of salt tolerance in maize plants - Sidra Jamil; Qasim Ali; Muhammad Iqbal; Muhammad Tariq Javed; Wasif Iftikhar; Faisal Shahzad; Rashida Perveen (Brazilian Journal of Botany, 2015)

Fulvic acid mediates chromium (Cr) tolerance in wheat (Triticum aestivum L.) through lowering of Cr uptake and improved antioxidant defense system - Shafaqat Ali; Saima Aslam Bharwana; Muhammad Rizwan; Mujahid Farid; Sidra Kanwal; Qasim Ali; Muhammad Ibrahim; Rafaqat Ali Gill; Muhammad Daud Khan (Environmental Science and Pollution Research, 2015)

Microbial contamination of drinking water in Pakistan—a review - Farhat Nabeela; Azizullah Azizullah; Roqaia Bibi; Syeda Uzma; Waheed Murad; Shakirullah Khan Shakir; Waheed Ullah; Muhammad Qasim; Donat-Peter Häder (Environmental Science and Pollution Research, 2014)

Comparative cytological and transcriptomic analysis of pollen development in autotetraploid and diploid rice - Jinwen Wu; Muhammad Qasim Shahid; Haibin Guo; Wei Yin; Zhixiong Chen; Lan Wang; Xiangdong Liu; Yonggen Lu (Plant Reproduction, 2014)

An efficient total synthesis of trilepisiumic acid - Aamer Saeed; Muhammad Qasim (Natural Product Research, 2014)

Total synthesis of cytotoxic metabolite ( ± )-desmethyldiaportinol from Ampelomyces sp. - Aamer Saeed; Muhammad Qasim (Natural Product Research, 2014)

Modelling land use change across elevation gradients in district Swat, Pakistan - Muhammad Qasim; Klaus Hubacek; Mette Termansen; Luuk Fleskens (Regional Environmental Change, 2013)

Chemical composition of essential oil from Calligonum polygonoides Linn. - Muhammad Qasim Samejo; Shahabuddin Memon; Muhammad Iqbal Bhanger; Khalid Mohammed Khan (Natural Product Research, 2013)

Abnormal PMC microtubule distribution pattern and chromosome behavior resulted in low pollen fertility of an intersubspecific autotetraploid rice hybrid - Jin-Hua He; Muhammad Qasim Shahid; Zhi-Xiong Chen; Xing-An Chen; Xiang-Dong Liu; Yong-Gen Lu (Plant Systematics and Evolution, 2011)

Gene structure and mutant alleles of PCDH15: nonsyndromic deafness DFNB23 and type 1 Usher syndrome - Zubair M. Ahmed; Saima Riazuddin; Sandar Aye; Rana A. Ali; Hanka Venselaar; Saima Anwar; Polina P. Belyantseva; Muhammad Qasim; Sheikh Riazuddin; Thomas B. Friedman (Human Genetics, 2008)